Respuesta :

hello : 
If f(x)=  3 ^x-1+ 4 and g(x) = 4x-7
 (f-g)(x) = f(x) - g(x)= 
3 ^x-1+ 4  - (4x - 7) 
(f-g)(x) =3 ^x-1-4x +11.....( answer : a)

Answer:

[tex](f-g)(x)=3^{x-1}-4x+11[/tex]

A is correct

Step-by-step explanation:

Given: [tex]f(x)=3^{x-1}+4[/tex]

[tex]g(x)=4x-7[/tex]

We are given two function and to find difference of two function

[tex](f-g)(x)[/tex]

[tex]\Rightarrow f(x)-g(x)[/tex]

[tex]\Rightarrow (3^{x-1}+4)-(4x-7)[/tex]

[tex]\Rightarrow 3^{x-1}+4-4x+7[/tex]

[tex]\Rightarrow 3^{x-1}-4x+11[/tex]

Hence, [tex](f-g)(x)=3^{x-1}-4x+11[/tex]